A STUDY OF ENGLISH LANGUAGE LEARNING STRATEGIES OF STUDENT TEACHERS AT NAKHON SAWAN RAJABHAT UNIVERSITY - Sangyok , Niphattha; Onthanee, Angkana; Jantakoon, Jakkrit (Journal of Graduate School Sakon Nakhon Rajabhat University, 2024)
The purpose of this research was to examine the English language learning strategies of student teachers at Nakhon Sawan Rajabhat University. The sample for this research, obtained through purposive sampling, consisted of 44 second-year student teachers who majored in Mathematics, with a good grade point average in the English language comparable to student teachers majoring in English, and no prior classroom interaction or participation. The instrument for data collection was a set of questionnaires adopted from Oxford’s Strategy Inventory for Language Learning (SILL) Version 7.0. The SILL was translated into the Thai language and adapted to suit the Thai context, achieving an Index of Item Objective Congruence (IOC) of 0.89 based on reviews by three experts. The SILL consists of six categories: 1. memory, 2. cognitive, 3. compensation, 4. metacognitive, 5. affective, and 6. social strategies. The statistics used in analyzing data were mean, and standard deviation. The research results revealed that student teachers employed all six aspects of language learning strategies at a medium level ( = 3.13, S.D.= 0.79). When considering each aspect, compensation strategies ( = 3.25, S.D. = 0.84) were most frequently employed, followed by metacognitive strategies ( = 3.24, S.D. = 0.94), affective strategies ( = 3.22, S.D. = 0.97), memory strategies ( = 3.12, S.D.= 0.84) and social strategies ( = 3.12, S.D. = 1.00) which had similar mean scores, whereas cognitive strategies ( = 2.83, S.D. = 0.94) were the least frequently utilized.